Factors Affecting Purchasing Decisions for Whiskas Brands at APS Petshop in Pangkep Regency - Andi Putri Tenriyola; Anis Anshari Mas'ud; Arifhan Ady DJ (MANDAR: Management Development and Applied Research Journal, 2023)
Product quality and variants are very important in influencing the purchasing decision when buying Whiskas at APS pet shop stores in Pangkep Regency. With the variety of products offered, consumers can choose the product they want. The purpose of this research is to examine and analyze the factors that impact the purchasing decisions of Whiskas products at APS pet shop stores in Pangkep Regency. The independent variables considered are Brand Image, Price Perception, and Promotion, while the dependent variable is the purchasing decision itself. For this study, primary data was collected through a survey involving 120 consumers, representing a sample from the total consumer base of 1850 people during the sales period from 2021 to 2022. The data were analyzed using the Statistical Product and Service Solutions (SPSS) Version 23 program. The findings of this study reveal a positive and significant relationship between brand image, price perception, and promotional influence on purchasing decisions for Whiskas brand products at APS pet shop stores in Pangkep Regency. Particularly, promotional factors were identified as having a dominant impact on the purchasing decisions for Whiskas brand products at APS pet shop stores in Pangkep Regency